Manajemen Peningkatan Mutu Kurikulum Melalui K13 Dan Kurikulum Merdeka - Umi Khoiroh, Anisya; Toyyibatin Nisak, Siti; Nur Aini, Intan; Juhairiyah, Juhairiyah; Nurhadi, Ali (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2025)
This article aims to examine in depth the management in improving the quality of the curriculum through the approach of the 2013 Curriculum (K13) and the Independent Curriculum. The method used in this study is a literature review (library research) by examining various academic sources, such as journals, books, and relevant education policy documents. The analysis focuses on how curriculum management is applied in the two curricula to answer the challenges of education quality in the global era. K13 offers a scientific learning approach and the strengthening of authentic assessments, while the Merdeka Curriculum gives freedom to educational units in designing contextual and student-centred learning. The results of the study show that the effectiveness of improving curriculum quality is highly dependent on strategic planning, adaptive implementation, and continuous evaluation in the curriculum management framework. Thus, strengthening managerial capacity at the level of educational institutions is a key factor in realizing a transformation of a quality curriculum that is relevant to the needs of the times.